Bilateral information sharing in oligopoly - Sergio Currarini; Francesco Feri (University of Innsbruck, Department of Public Finance, 2007)
We study the problem of information sharing in oligopoly, when sharing decisions are taken before the realization of private signals. Using the general model developed by Raith (1996), we show that if firms are allowed to make bilateral exclusive sharing agreements, then some degree of information sharing is consistent with equilibrium, and is a constant feature of equilibrium when the number of firms is not too small. Our result is to be contrasted with the traditional conclusion that no information is shared in common values situations with strategic substitutes - such as Cournot competition with demand shocks - when firms can only make industry-wide sharing contracts (e.g., a trade association).
Keywords: D43; D82; D85; L13; 330; information sharing; oligopoly; networks; Bayesian equilibrium; Wissenstransfer; Unvollkommener Wettbewerb; Oligopol; Allgemeines Gleichgewicht; Bayes-Statistik